Massive hemoptysis in Loeys–Dietz syndrome. Issue 3 (27th November 2015) - Bennett, Christopher L.; Aziz, Hamza; Sparks, Elizabeth; Shah, Trushil; Yoder, Mark; MacCarrick, Gretchen; Dietz, Harry C.
Abstract : We describe four unrelated individuals with Loeys–Dietz syndrome (LDS) who presented with massive hemoptysis of unknown etiology. LDS is an autosomal dominant connective‐tissue disorder characterized by altered cardiovascular, craniofacial, and skeletal development that is attributed to mutations in the TGFBR1, TGFBR2, SMAD3, or TGFB2 genes. Massive hemoptysis (MH) is a rare and often fatal pulmonary medical emergency. This is the first report of MH in individuals with LDS and establishes it as part of the LDS spectrum. It compels providers to educate their LDS patients on MH, although much investigation needs to be done to determine etiology and appropriate treatment for this newly described LDS feature. © 2015 Wiley Periodicals, Inc.